Financial Inclusion and its Impact on Poverty Alleviation amongst Micro and Small Enterprises in Cameroon - Esowe, Susannash Limunga (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">An inclusive and stable financial system promotes investments and a market driven economy which is productive and competitive. Appropriate financial access at an affordable cost is indispensable for the growth of MSEs as well as the financial wellbeing of the MSE operators. About 80% of the population in Cameroon operates in the informal sector, while about 98.5% of MSEs hardly have access to regulated finances, hence suffer from financial exclusion and poverty. This study seeks to analyze the extent to which financial inclusion can impact poverty alleviation among MSE operators in Cameroon. The relevant data for this study were sourced with the use of a closed ended structured questionnaire. Data analysis was by statistical inferences and modelling involving multiple regressions by the use of AMOS 24. The findings from the analysis reveals that financial knowledge and financial wellbeing have a significant positive influence on poverty alleviation amongst MSE operators in Cameroon. This study highlights that policy makers should promote the putting in place of financial literacy mechanisms and structures to facilitate the users of financial instruments better acquaint themselves with knowledge on the existent financial instruments as well as their proper usage.